Neurotransmitters Affect Larval Development by Regulating the Activity of Prothoracicotropic Hormone-Releasing Neurons in Drosophila melanogaster - Hao, Shun; Gestrich, Julia Yvonne; Zhang, Xin; Xu, Mengbo; Wang, Xinwei; Liu, Li; Wei, Hongying (Frontiers in Neuroscience, 2021)
Ecdysone, an essential insect steroid hormone, promotes larval metamorphosis by coordinating growth and maturation. In Drosophila melanogaster, prothoracicotropic hormone (PTTH)-releasing neurons are considered to be the primary promoting factor in ecdysone biosynthesis. Recently, studies have reported that the regulatory mechanisms of PTTH release in Drosophila larvae are controlled by different neuropeptides, including allatostatin A and corazonin. However, it remains unclear whether neurotransmitters provide input to PTTH neurons and control the metamorphosis in Drosophila larvae. Here, we report that the neurotransmitters acetylcholine (ACh) affect larval development by modulating the activity of PTTH neurons. By downregulating the expression of different subunits of nicotinic ACh receptors in PTTH neurons, pupal volume was significantly increased, whereas pupariation timing was relatively unchanged. We also identified that PTTH neurons were excited by ACh application ex vivo in a dose-dependent manner via ionotropic nicotinic ACh receptors. Moreover, in our Ca2+ imaging experiments, relatively low doses of OA caused increased Ca2+ levels in PTTH neurons, whereas higher doses led to decreased Ca2+ levels. We also demonstrated that a low dose of OA was conveyed through OA β-type receptors. Additionally, our electrophysiological experiments revealed that PTTH neurons produced spontaneous activity in vivo, which provides the possibility of the bidirectional regulation, coming from neurons upstream of PTTH cells in Drosophila larvae. In summary, our findings indicate that several different neurotransmitters are involved in the regulation of larval metamorphosis by altering the activity of PTTH neurons in Drosophila.